2013
DOI: 10.1172/jci64768
|View full text |Cite
|
Sign up to set email alerts
|

67-kDa laminin receptor increases cGMP to induce cancer-selective apoptosis

Abstract: The 67-kDa laminin receptor (67LR) is a laminin-binding protein overexpressed in various types of cancer, including bile duct carcinoma, colorectal carcinoma, cervical cancer, and breast carcinoma. 67LR plays a vital role in growth and metastasis of tumor cells and resistance to chemotherapy. Here, we show that 67LR functions as a cancer-specific death receptor. In this cell death receptor pathway, cGMP initiated cancer-specific cell death by activating the PKCδ/acid sphingomyelinase (PKCδ/ASM) pathway. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
226
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(237 citation statements)
references
References 45 publications
10
226
0
1
Order By: Relevance
“…The absence of cGKI and an increase of the cGMP level could lead to the activation of other kinases, such as PKA (47) or PKC (49). PKCII␤, indeed, in our dataset, showed high regulation at the phosphorylation level of the activation loop site (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…The absence of cGKI and an increase of the cGMP level could lead to the activation of other kinases, such as PKA (47) or PKC (49). PKCII␤, indeed, in our dataset, showed high regulation at the phosphorylation level of the activation loop site (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…When a PDE5-selective inhibitor, vardenafil, was also added to cultured cells, it synergized with EGCG to reduce the IC 50 of EGCG from 23.2 to 1.4 mmol/L. Such synergy was also observed in xenograft tumors (20).…”
Section: Synergistic Actions From Combination Of Chemopreventive Agentsmentioning
confidence: 87%
“…A good example for showing synergistic effect between two agents was recently provided by Kumazoe and colleagues (20). These authors showed that (À)epigallocatechin 3-gallate (EGCG) activated 67-kDa laminin receptors in multiple myeloma cells.…”
Section: Synergistic Actions From Combination Of Chemopreventive Agentsmentioning
confidence: 99%
“…Based on previous evidence, they presented a new concept: green tea catechins as synergists with anticancer drugs. Kumazoe et al (2013) also reported the synergistic effect on cancer inhibition between EGCG and anti-cancer agents. EGCG activated 67-kDa lamina receptors in multiple myeloma cells, resulting in elevated cyclic guanosinc monophosphate (cGMP) levels, which initiated apoptosis through the activation of protein kinase C-δ (PKCδ) and acid sphingomyelinase in a novel death pathway.…”
Section: Structural Modifications Of Catechinsmentioning
confidence: 96%